(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the concept of lexicology, which is considered the main branch of linguistics, types of meanings, the issue of semantic field, its place in science, lexicography, phraseology, semasiology, semantics, etymology, stylistics concepts, and thoughts about the essence and structure of words in lexicology.